KEPUTUSAN PEMBELIAN E-COMMERCE TOKOPEDIA PADA GENERASI Z DI KOTA DEPOK - Sarah Anissa Putri Lestari (2020)
This study uses a quantitative descriptive method which was carried out on Generation Z users of Tokopedia in Depok City. Tokopedia is an e-commerce company (electronic commerce) type of marketplace from Indonesia which was officially launched to the public on August 17, 2009 and Generation Z are people born in 1995-2010. The purpose of this research is to find out and analyze whether the promotion, price, and quality of service affect the decision to buy Tokopedia e-commerce in generation Z in Depok City. Samples taken were 96 respondents with the side probability method. Data collection was carried out by distributing questionnaires. The data analysis technique used is descriptive analysis and inferential analysis with the analytical tool used is PLS (Partial Least Square). The results showed that (1) Promotion has no effect on purchasing decisions. (2) Price has an influence on purchasing decisions. (3) Service quality has an influence on purchasing decisions. The result of R-Square purchasing decision is 0.762, indicating a very strong research model and means that promotion, price, and service quality together have a real contribution to the purchase decision Tokopedia e-commerce is 76.2%.